Inheritance of white, black and brown coat colours in alpaca (Vicuna pacos L.) - Valbonesi, Alessandro; Apaza, Nolberto; La Manna, Vincenzo; Gonzáles Castillo, Mario Lino; Huanca Mamani, Teodosio; Renieri, Carlo (Elsevier, 2022)
An experimental trial of the segregation of white vs. pigmented and black vs. brown colours in alpacas was conducted at the Peruvian INIA Quimsachata Experimental Station. One hundred and forty five offspring were born from the following matings: 4 white sires × 36 white dams, 4 white sires × 39 pigmented dams, and 9 pigmented sires × 70 pigmented dams. Among these last matings were, 4 black sires × 25 black dams, 2 black sires × 20 brown dams, and 3 brown sires × 25 brown dams. Statistical tests validate that the inheritance of white is due to a single gene which is dominant over pigmentation, without any modifying effect and independent of segregation of black and brown patterns. However, the evidence does not support a simple dominant inheritance of the black vs. brown.